Molecular Characterization of Chicken Anemia Virus Circulating in Chicken Flocks in Egypt - Mohammed AboElkhair; Alaa G. Abd El-Razak; Abd Elnaby Y. Metwally (Advances in Virology)
Introduction. Although many previous studies reported detection of chicken anemia virus (CAV) in Egypt since 1990, genomic characterization of this circulating CAV has not been published. In the present study, four nucleotide sequences of detected CAV were genetically characterized. Methods. These nucleotide sequences were obtained from commercial chicken flocks in two different locations of Egypt during 2010. The target region for sequencing was 675 bp nucleotide of partial coding region of VP1 protein. The nucleotide and deduced amino acid sequences of the detected CAV were aligned and compared to worldwide CAV isolates including commonly used vaccine strains. Phylogenetic analysis of these sequences was also carried out. Results. Our results showed that all the Egyptian CAV sequences were grouped in one group with viruses from diverse geographic regions. This group is characterized by amino acids profile 75I, 97L, 139Q, and 144Q in VP1. The phylogenetic and amino acid analyses of deduced amino acid indicated that the detected CAV sequences differ from CAV vaccine strains. Conclusion. This is the first report that describes molecular characterization of circulating CAV in Egypt. The study showed that the detected CAV, in Egypt are field viruses and unrelated to vaccine strains.